The association between TaqI A polymorphism of ANKK1 (DRD2) gene and ADHD in the Czech boys aged between 6 and 13 years - Paclt, Ivo; Drtilkova, Ivana; Kopeckova, Marta; Theiner, Pavel; Serý, Omar; Cermakova, Nikol (Neuro endocrinology letters, 2010)
OBJECTIVE: The purpose of this study was the correlation of the combined type of ADHD in children and Taq IA polymorphism DRD2 gene. We hypothesized a positive correlation of DRD2 polymorphisms in the combined type of ADHD patients without co-morbidity. PATIENTS AND METHODS: Our research sample included 586 unrelated boys of the Czech origin aged between 6 and 13 years. The ADHD group consisted of 269 boys and the control group consisted of 317 boys. PCR detection of the DRD2 polymorphism was carried out by using primers, described by Grandy (Grandy et al. 1989). RESULTS: The comparison of genotype frequencies showed statistically highly significant difference between the studied groups (p<0.0001). A statistically significant difference was also found when the allelic frequencies between the two groups were compared (p<0.0001), with the A1 allele having a 4.359 fold higher risk of ADHD (Risk Ratio=4.359, 95% CI of RR=3.5753 to 5.3144, Odds Ratio= 7.7824; 95% CI of OR=10.315 to 13.6719). CONCLUSIONS: Our results presented a highly positive correlation between the combined type of ADHD without co-morbidity and ANKK l (DRD2) polymorphism .
Keywords: Deoxyribonucleases, Type II Site-Specific; Attention Deficit Disorder with Hyperactivity; Humans; Polymorphism, Restriction Fragment Length; dítě; Child; hyperkinetická porucha; Receptors, Dopamine; protein-serin-threoninkinasy; frekvence genu; Genotype; lidé; receptory dopaminu D2; receptory dopaminové; Protein Serine-Threonine Kinases; restrikční endonukleasy typu II; Male; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; Gene Frequency; genotyp; polymorfismus délky restrikčních fragmentů; Česká republika; mužské pohlaví; mladiství; Receptors, Dopamine D2